WE ALL BECOME THE OFFERING: RATAN THIYAM’S CHAKRAVYUHA AND CONTEMPORARY MANIPUR - Premchandra, Kshetrimayum (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper delves into the subtext of the chakravyuha episode in the Mahabharata and examines how Ratan Thiyam transforms it into a play that mirrors the socio-political landscape of Manipur across time. Thiyam’s Chakravyuha undeniably offers a political commentary on Manipur, metaphorically portraying the struggles faced by Manipuri youths, akin to the fate of the helpless Abhimanyu. He illustrates how these young individuals are ensnared by powerful forces, forced into violence not as conquerors or victims, but as sacrificial pawns. In this light, the play serves as a poignant reflection on the entrapment of youth in cycles of conflict, providing a powerful critique of contemporary realities which have become notorious in recent times. The depiction of violence on the Manipuri stage is not a recent phenomenon. Political dramas have long captivated Manipuri audiences, resonating deeply with their experiences. This paper examines the factors that made this politically charged play significant in the 1980s, and why it remains even more relevant today. Furthermore, it delves into the interconnected themes of violence, human suffering, sectarianism, ethnic divisions, and other critical issues that are pivotal in shaping Manipur's future.